Influence of Development of the Bantayan Coastal Area On the Level of Community Welfare: A Case Study at Bantayan Beach, North Aceh Regency - Muhammad Ali; Mursalin; Deddi Satria M (LPPM Universitas Malikussaleh, 2022)
Bantayan Beach tourist attraction in Gampong Bantayan, Seunuddon Subdistrict, North Aceh Regency is becoming an Islamic tourist destination. This is an area that has received more attention from the North Aceh District government. Given that this area is included in the eastern coastal area of North Aceh Regency. The development of coastal areas is the concern of various parties to create and make good changes such as decorating parks, creating relaxing places and making every coastal context a particular attraction for visitors. As well as what the government has done through the North Aceh Youth, Sports and Tourism Office (Disporapar), it has also built supporting facilities such as two food outlets, prayer rooms, and bathing and washing facilities. The village government began to realise that its area was a place of visit for every citizen in various life events, for example every weekend and the day facing the fasting month of Ramadan to carry out activities to enjoy the beauty of the beach with family with the term in the village called 'Meuramin', this is a good and constructive momentum to create economic potential in the local area. Based on this, researchers are interested in further examining the effect of the development of the coastal area of bantayan beach on the level of community welfare. The research method used is descriptive qualitative with the sample being community members who are in the coastal area near the bantayan beach. Data collection techniques using questionnaires and location surveys. This research proposal has a high novelty, because similar studies have never been carried out, especially the study of the coastal area of Bantayan Beach in North Aceh Regency. The benefit of this research is to provide a concrete basis of information and data analysis for policy makers, especially related agencies and stakeholders relevant to this study. In addition, the benefits of this research also increase knowledge and insight and become a reference for further researchers who are concerned with tourism in coastal areas.